2022
DOI: 10.1101/2022.01.17.476610
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cell morphological profiling enables high-throughput screening for PROteolysis TArgeting Chimera (PROTAC) phenotypic signature

Abstract: PROTACs (PROteolysis TArgeting Chimeras) use the ubiquitin-proteasome system to degrade a protein of interest for therapeutic benefit. Advances in targeted protein degradation technology have been remarkable with several molecules moving into clinical studies. However, robust routes to assess and better understand the safety risks of PROTACs need to be identified, which is an essential step towards delivering efficacious and safe compounds to patients. In this work, we used Cell Painting, an unbiased high cont… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…The pharmaceutical industry needs disruptive technologies to rapidly reduce the cost and failure rates for getting life-changing medicines to patients. The image-based microscopy profiling assay, Cell Painting 1 , has shown promise in several steps in the drug discovery pipeline 2 , including disease phenotype identification 3 , hit identification 4,5 assay activity prediction 6 , toxicity detection 7,8 and mechanism of action determination 9 , as well as in basic biological research such as functional genomics 10 . In this assay, eight cellular components are stained with six inexpensive dyes and imaged in five channels on a fluorescence microscope.…”
Section: Introductionmentioning
confidence: 99%
“…The pharmaceutical industry needs disruptive technologies to rapidly reduce the cost and failure rates for getting life-changing medicines to patients. The image-based microscopy profiling assay, Cell Painting 1 , has shown promise in several steps in the drug discovery pipeline 2 , including disease phenotype identification 3 , hit identification 4,5 assay activity prediction 6 , toxicity detection 7,8 and mechanism of action determination 9 , as well as in basic biological research such as functional genomics 10 . In this assay, eight cellular components are stained with six inexpensive dyes and imaged in five channels on a fluorescence microscope.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, PROTAC phenotypic signatures have already been identified through cell morphological profiling. 186 3.4. Preparing Data for AI/ML-Enabled Analysis of Phenotypic Screening Data.…”
Section: Maximizing the Depth Of Downstream Analysismentioning
confidence: 99%
“…These numerical features representing morphological properties such as shape, size, area, intensity, granularity, and correlation, among many others, are considered versatile biological descriptors of a system. 7 Previous studies have shown Cell Painting data to be predictive of a wide range of bioactivity and drug safety-related endpoints such as the mechanism of action 14 , cytotoxicity 24 , microtubule-binding activity 15 , and mitochondrial toxicity 25 , and has been used to identify phenotypic signatures of PROteolysis TArgeting Chimeras (PRO-TACs) 16 as well as determining the impact of lung cancer variants 17 . Thus Cell Painting data can be expected to contain a signal about the biological activity of the compound perturbation, 7 and in this work, we explored how best to combine Cell Painting and chemical structural models for the prediction of a wide range of biological assay outcomes.…”
Section: Mainmentioning
confidence: 99%